Psychosocial and mental health status among older adults in China during the COVID-19 pandemic: A cross-sectional study - Sheng Luo; Yulin Chai; Xiaohui Yang; Mengxue Wang; Lin Wang; Yuxi Wang; Yuxiu Liu (Acta Psychologica)
Background: On March 11, 2020, the World Health Organization (WHO) declared COVID-19 a pandemic. During the virus's spread and subsequent lockdowns, older adults faced heightened risks and significant mental health challenges. Methods: A cross-sectional study was conducted in Shandong Province, China, using a custom-designed demographic questionnaire, a COVID-19-related survey, and the Symptom Checklist-90 Revised (SCL-90-R). Correspondence analysis and multiple linear regression models were employed to examine factors influencing the mental health of older adults. Results: Among 3363 older adults, the total SCL-90-R score was 153.11 ± 36.98, with an average score of 1.70 ± 0.41. Both scores were lower than the Chinese norm and pre-pandemic levels. Factors significantly affecting older adults' mental health included place of residence, age, educational attainment, marital status, fear of COVID-19, understanding of COVID-19 transmission routes, and awareness of preventive measures. Conclusions: Greater attention is needed to address the mental health of older adult males, individuals of advanced age, employed individuals, those with lower educational backgrounds, and those without a spouse. Policymakers should implement targeted policies and interventions to enhance mental health support for older adults.